Exploring the High Performance Computing-Enablement of a Suite of Gene-Knockout Based Genetic Engineering Applications - Li, Zhenya; Sinnott, Richard O.; Choon, Yee Wen; Sjaugi, Muhammad Farhan; Mohd Saberi, Mohamad; Safaai, Deris; Suhaimi, Napis; Omatu, Sigeru; Corchado, Juan Manuel; Zuwairie, Ibrahim; Zulkifli, Md. Yusof (Springer International Publishing, 2016)
Genetic engineering provides methods to modify the genes of microorganisms to achieve desired effects. This can be done for improved organism growth rate or increasing production yield of a desired gene product. Gene knockout is a technique that can improve the specific characteristics of microorganisms by disabling selected sets of genes. However, microorganisms are complex and predicting the effects of gene modification is difficult. Several algorithms have been proposed to support a range of gene knockout strategies, including BAFBA, BHFBA and DBFBA. In this paper, scaling these algorithms and methods to utilise High Performance Computing (HPC) resources have been explored. The applications have been parallelized on HPC and the scalability and performance of these approaches were explored and documented.